Relationship Between Knowledge Attitude with Hazard Protective Behavior Using Pesticides of Sugarcane Farmers Nong Hong District, Buriram Province - Wongsutha, Sutthida; Kaiyasook, Natnisa; Seangprom, Nipawan; Kokkrathok, Nattawut (Health Science Journal of Nakhon Ratchasima College, 2022)
This purpose survey research were to study the relationship between knowledge, attitude with hazard protective behavior use pesticides of sugarcane growers Nong Hong District, Buriram Province. The sample were sugarcane growers consisted of 274 people selected by purposive sampling. All data were collected form the test and questionnaire by researcher. Mean, Percentages, Standard Deviation and Pearson product moment correlation were used for the data analysis by a computer program. The results were as follows: 1. The knowledge of using pesticides for sugarcane farmers had no correlation with hazard protective behavior use pesticides of sugarcane farmers Nong Hong District, Buriram Province. 2. The attitude of using pesticides for sugarcane farmers correlated negative with hazard protective behavior use pesticides of sugarcane farmers Nong Hong District, Buriram Province at 0.05 level (p-value = 0.040).